Papulo-pustuleznaja form rosacea – results of immunohistochemical research of the condition of thelesions. - Haritonova, E. G.; Sviatenko, T. V. (Морфологія / Morphologia / Morfologìâ, 2012)
Studying and the analysis of links pathogenesis papulo-pustulosis forms of rosacea by means of a wide spectrum of immunohistochemical markers became a research problem. For the decision of tasks in view by the author it is used biopsy a material of 11 diagnosed cases papulo-pustulosis forms of rosacea at me at the age from 32 till 59 years. Use of immunohistochemical methods of research has allowed to reveal new links in pathogenesis of rosacea and to establish a role of some cellular populations of a skin and cages of immune system in progressing of disease and development papulo-pustulosis forms of rosacea. Authors have come to a conclusion that is possible, strengthening of pathological changes at papulo-pustulosis forms of rosacea is caused by presence of pincers which are capable to cause migration in skin CD68+ cages while quantity CD138+ plasmocytes was insignificant and didn’t exceed 5-10 % in infiltrates. Кi-67+ cages in a considerable quantity were as a part of sebaceous glands that specified in progressing hyperplastic changes in these appendages of a skin. Besides, the quantity of cages, positive on this marker, correlated with expressiveness of defeat of sebaceous glands in a greater degree, than with a disease stage.